ANALYSIS OF MASS CCD OBSERVATIONS TO IMPROVE THE ACCURACY OF ASTROMETRIC PROCESSING - Protsyuk, Yu.; Kovalchuk, O. (Одеські астрономічні публікації, 2018)
In Research Institute: Mykolaiv Astronomical Observatory (RI MAO) regularly observations of fields with open clusters on the KT50 telescope (D = 500 mm, F = 3000 mm) with an Alta U9000 CCD camera (3k × 3k, FOV 42.6' × 42.6') in drift scan mode are carried out. For this observation mode, we investigated the dependence of the differences between observed minus calculated (O-C) angular coordinates of reference stars in depending on X coordinate (direction perpendicular to the direction of charge transfer) in the CCD coordinate system. The data of observations of open clusters obtained in the RI MAO in 2011-2017 were used for the study. The data array used to obtain the distribution (O-C) for right ascension (RA) and declination (DEC), depending on X, contains 62 million single observations of stars. The processing of the original data was carried out using the Astrometrica program with the reference catalogue UCAC4. The distribution of the (O-C) value as a function of X according to RA and DEC was obtained by the method of least squares. For the solution is a 10th-degree polynomial of X and a third degree from the integral intensity of the object in the image was used. The study showed the presence of significant (0.01-0.02)" systematic errors in the field of the matrix for bright stars (10-12)m. For faint stars, the amplitude of the constant part decreases significantly while maintaining the periodic component. Similar studies have also been carried out for a lot of CCD frames obtained from astronomical databases for other instruments. The results will be used to improve the accuracy of astrometric catalogues obtained with the KT50 telescope and to improve the accuracy of the proper motions of stars in the vicinity of open clusters.